Saturday

April 19, 2014

April 19, 2014

Posted by **Al** on Friday, September 16, 2011 at 3:20am.

2x-6y=3 (1)

4x+9y=-1 (2)

- Algebra -
**Anonymous**, Friday, September 16, 2011 at 4:00amMultiply first equation with -2

- 4 x + 12 y = -6

Note that, if you add down, the y's will cancel out.

- 4 x + 12 y = - 6

4 x + 9 y = - 1

( - 4 x + 4 x ) + ( 12 y + 9 y ) = -6 + ( -1 )

0 + 21 y = -6 - 1

21 y = - 7 Diwide both sides with 21

y = - 7 / 21

( Remark: 7 / 21 = 1 / 3 )

y= - 1 / 3

First equation:

2 x - 6 y = 3

2 x - 6 * ( - 1 / 3 ) = 3

2 x + 6 / 3 = 3

2 x + 2 = 3

2 x = 3 - 2

2 x = 1 Divide both sides with 2

x = 1 / 2

x = 1 / 2 , y= - 1 / 3

- Algebra -
**KK**, Friday, September 16, 2011 at 4:05pmThank You

**Related Questions**

Algebra 2 - maximize p=6x+10y minimize p=14x+9y use elimination to solve: 4x+5y=...

Algebra II-Please check my solution - Solve by elimination method-thanks fro ...

algebra 1 - I'm stuck on this problem. Can you help? -4x-9y=1 -x + 2y =-4 WHat ...

Algebra - Solve by elimination method. 2x+ 3y = 1 4x + 6y= 2

Algebra - Solve using the elimination method. 2x +3y = 2, 4x + 6y =4.

AP Calc for Reiny - You did just fine and your second derivative is correct, if ...

AP Calc for Reiny - You did just fine and your second derivative is correct, if...

Algebra - Solve the following system of linear equations: 2x - 3y + 6z = -12 5x...

Math help - Solve using substitution 3x - 9y = 3 6x - 3y = -24 Solve using ...

Math - Solve using substitution 3x - 9y = 3 6x - 3y = -24 Solve using ...